Patient engagement in the process of planning and designing outpatient care improvements at the Veterans Administration Health‐care System: findings from an online expert panel - Khodyakov, Dmitry (Health Expect, 2016)
CONTEXT: There is a strong interest in the Veterans Administration (VA) Health‐care System in promoting patient engagement to improve patient care. METHODS: We solicited expert opinion using an online expert panel system with a modified Delphi structure called ExpertLens(™). Experts reviewed, rated and discussed eight scenarios, representing four patient engagement roles in designing and improving VA outpatient care (consultant, implementation advisor, equal stakeholder and lead stakeholder) and two VA levels (local and regional). Rating criteria included desirability, feasibility, patient ability, physician/staff acceptance and impact on patient‐centredness and care quality. Data were analysed using the RAND/UCLA Appropriateness Method for determining consensus. FINDINGS: Experts rated consulting with patients at the local level as the most desirable and feasible patient engagement approach. Engagement at the local level was considered more desirable than engagement at the regional level. Being an equal stakeholder at the local level received the highest ratings on the patient‐centredness and health‐care quality criteria. CONCLUSIONS: Our findings illustrate expert opinion about different approaches to patient engagement and highlight the benefits and challenges posed by each. Although experts rated local consultations with patients on an as‐needed basis as most desirable and feasible, they rated being an equal stakeholder at the local level as having the highest potential impact on patient‐centredness and care quality. This result highlights a perceived discrepancy between what is most desirable and what is potentially most effective, but suggests that routine local engagement of patients as equal stakeholders may be a desirable first step for promoting high‐quality, patient‐centred care.